MARKETING STRATEGY OF DUCK COFEED - Y.A.E., Prasetyo; Putri, B. R. T.; Roni, N.G.K. (Jurnal Peternakan Tropika, 2023)
This study aims to analyze the internal and external environmental factors that influence the marketing strategy of Duck Cofeed. This research is a case study conducted at the production house of Duck Cofeed Kerambitan, Tabanan Regency. The number of respondents was 7 people, consisting of 2 practitioners respondents, 3 academic respondents in the field of animal husbandry, and 2 decision makers respondents. Sources of data used are primary and secondary data. Data were collected through observation, in depth interviews and interviews with the help of questionnaires. There are 3 analyzes used, namely, 1) internal and external analysis of the business to find the strengths, weaknesses, opportunities and threats that will be included in the IFE and EFE matrices; 2) IE matrix used to determine business position; 3) SWOT analysis is used to develop alternative marketing strategies for Duck Cofeed. The results of the IFE and EFE analysis of this study indicate that the position of the Duck Cofeed is in the IX cell in the IE matrix and is in the 3rd group with harvest division and divestment.raw materials Duck Cofeed by maintaining high nutrition and an affordable selling price with a TAS value of 1.53. Keywords: marketing strategy, duck cofeed, SWOT, QSPM